A COMPARATIVE ANALYSIS BETWEEN WESTERN BALKAN COUNTRIES AND SELECTED OECD COUNTRIES (2010 - 2019) OF THE EFFECT OF UNEMPLOYMENT ON NON-PERFORMING LOAN - Ercan Özen; Ajshe Komoni; Fisnik Morina; Simon Grıma; İbish Mazreku (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The main purpose of this paper is to determine the effect of unemployment on non-performing loans through a comparative analysis between the Western Balkans countries and some selected OECD countries. The size of non-performing loans (NPLs) plays a key role in the stability of the banking sector of a country. Macroeconomic factors that explain the NPLs contain very important information for banks as well as for a country and studies in this regard, which compare developing countries and already developed ones have received little attention. To carry out this study, panel data and quantitative econometric models have been applied, specifically Linear Regression, Random Effect, Fixed Effect, Huasman - Taylor Regression and Generalized Estimating Equations (GEE Model) on secondary data from official reports of the World Bank, Organization for Economic Cooperation and Development, during the period from 2010 to 2019. Based on economic theory and our findings, we can say that the relationship between the unemployment rate and non-performing loans is directly proportional: an increase in the unemployment rate will lead to an increase in the non-performing loan rate. Moreover, Findings show that controlling the rate of unemployment helps in controlling the level of non-performing loans